Al-Waʻyu al-Ẓātī li al-Țalabah fī Taʻlīmi al-Lugah al-ʻArabiyyah fī Jāmi’ati Ma’ārif Lampung - Dian Risky Amalia; Jauharotun Nafisah; Siti Sulaikho; Nafi’atu Rohmah (KURAS Institute, 2024)
Arabic learning is complex and has many obstacles, requiring all parties involved to deal with it. Today's most crucial obstacle in learning Arabic is that students' awareness of the importance of Arabic has yet to be fully formed. This study aims to describe students' self-awareness in learning Arabic. The research method is qualitative. Data collection will be done using interviews, observation, and documentation. Moreover, data analysis used Miles and Huberman's steps, data collection, simplification, exposure, and retrieval. The result of the research is that students experience de-individuation, which is losing their self-identity and merging with social identity, while the indication is that some students do not know their strengths and weaknesses in learning Arabic. These two indicators result in a low sense of responsibility and individual guilt, so most students have not been able to reflect on what they have and what they do not have and have not been able to evaluate themselves, which means being able to check and correct again the work that has been done.